Diaspora and Media in Europe
XV, 192 p. 6 illus. in color.
Keywords: This book examines how African, Asian, Middle Eastern and Latin American diasporas use media to communicate among themselves and to integrate into European countries. Whereas migrant communities continue employing print and broadcasting technologies, the rapidly growing applications of Internet platforms like social media have substantially enriched their interactions. These communication practices provide valuable insights into how diasporas define themselves. The anthology investigates varied uses of media by Ecuadorian, Congolese, Moroccan, Nepalese, Portugal, Somali, Syrian and Turkish communities residing in Belgium, Germany, Italy, the Netherlands, Spain, Sweden and the UK. These studies are based on research methodologies including big data analysis, content analysis, focus groups, interviews, surveys and visual framing, and they make a strong contribution to the emerging theory of diasporic media.